A man filling wet drug jars in an apothecary shop (1650)
In the apothecary's workshop a man pours liquid from a jar into blue earthenware vessels. He is surrounded by copper bowls, jars, and sacks of endive and other herbs and vegetables likely used for medical preparations and tonics. At far right a bowl of vegetables sits beside a furnace with a distillation apparatus. Crates and baskets for travel lie on the ground at left, where another assistant emerges from the shadows.
Keywords: Alchemists; Alchemy; Alchemy in art